2011
DOI: 10.5486/pmd.2011.4579
|View full text |Cite
|
Sign up to set email alerts
|

On measurable solutions of a general functional equation on topological groups

Abstract: We establish a theorem of the type "measurability implies continuity" for solutions f of the functional equationunder reasonable conditions upon the integers αi, βi and the mappings Γ, Φ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Baron in [3] showed that if G is a metrizable topological group and f : G ℝ is Baire measurable and satisfies (1.2) then f is continuous. Kochanek and Lewicki (see [4]) proved that if G is metrizable locally compact group and f : G ℝ is Haar measurable and satisfies (1.2), then f is continuous. As already mentioned in [2], Kochanek noticed that every function f defined on an abelian group G which is of the form f = g ∘ a, where g : ℝ ℝ is a solution of (1.2) described by Theorem 1.1 and a: G ℝ is an additive function, is a solution of…”
Section: Introductionmentioning
confidence: 99%
“…Baron in [3] showed that if G is a metrizable topological group and f : G ℝ is Baire measurable and satisfies (1.2) then f is continuous. Kochanek and Lewicki (see [4]) proved that if G is metrizable locally compact group and f : G ℝ is Haar measurable and satisfies (1.2), then f is continuous. As already mentioned in [2], Kochanek noticed that every function f defined on an abelian group G which is of the form f = g ∘ a, where g : ℝ ℝ is a solution of (1.2) described by Theorem 1.1 and a: G ℝ is an additive function, is a solution of…”
Section: Introductionmentioning
confidence: 99%
“…Baron for (1). Lebesgue measurable solutions of (1), and in fact Haar measurable solutions of much more general equations, were considered by T. Kochanek and M. Lewicki in [3]. We consider Baire measurable solutions of…”
mentioning
confidence: 99%